2003
DOI: 10.1124/dmd.31.4.491
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Metabolism of a COX-2 Inhibitor, Valdecoxib, in Mice

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:The pharmacokinetics and metabolism of valdecoxib, a potent cyclooxygenase-2 selective inhibitor, were investigated in mice. Valdecoxib, 4-(5-methyl-3-phenylisoxazol-4-yl)benzenesulfonamide, is a new anti-inflammatory drug that is highly selective for inhibition of the inducible form of cyclooxygenase (COX-2 1 ) in in vitro enzymatic assays (Talley et al., 2000). This drug (BEXTRA, Pharmacia Corporation) was approved recently by the U.S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…This suggested that M0 might be a GSH-related metabolite of DCNB. Actually, the structure analysis by LC-MS/MS revealed that M0 was the GSH-related metabolite, the methylsulfone-N-acetyl form (Bray et al, 1957a,b;Zhang et al, 2003). Considering these results, Gstm1-null mice administered the specific substrate for mouse GSTM1, such as DCNB, are highly exposed and toxicologically susceptible to the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that M0 might be a GSH-related metabolite of DCNB. Actually, the structure analysis by LC-MS/MS revealed that M0 was the GSH-related metabolite, the methylsulfone-N-acetyl form (Bray et al, 1957a,b;Zhang et al, 2003). Considering these results, Gstm1-null mice administered the specific substrate for mouse GSTM1, such as DCNB, are highly exposed and toxicologically susceptible to the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of this mass fragmentation depicts that the substrate underwent hydroxylation of 3-phenyl ring, and thus, the product was identified as 4-[3-(4-hydroxyphenyl)-5-methyl-4-isoxazolyl] benzenesulfonamide. These products were also formed as metabolites of valdecoxib in mice [12]. M3 was also formed in humans in a disposition study performed by Yuan et al [3].…”
Section: Biotransformation Of Valdecoxibmentioning
confidence: 95%
“…Oral administration of creatine produced a dose-dependent improvement in motor performance and extended survival in G93A transgenic mice, while it protected the loss of both motor neurons and substantia nigra neurons at 120 days of age [69]. It has recently been reported that the neuroprotective effects of creatine may be additively enhanced with minocycline and COX-2 inhibitors in ALS mice [74,75]. It has recently been reported that the neuroprotective effects of creatine may be additively enhanced with minocycline and COX-2 inhibitors in ALS mice [74,75].…”
Section: Bioenergetic Compounds Ameliorating Oxidative Stress and Mitmentioning
confidence: 99%